Computational investigation of high-order mode localization in electrostatically coupled microbeams with distributed electrodes for high sensitivity mass sensing. (September 2021) - Lyu, Ming; Zhao, Jian; Kacem, Najib; Tang, Bin; Liu, Pengbo; Song, Jiahao; Zhong, Heng; Huang, Yu
Graphical abstract: Highlights: Nonlinear dynamics of high-order mode-localized mass sensor is investigated. Ultrasensitive mass sensor is designed based on the high order mode localization. The model is established, solved using ANM and HBM and verified by the LTI method. Sensitivity is beyond two times larger than full electrode sensor. Sensitivity can be improved compared with low order-mode localization. Abstract: The high-order mode localization in electrostatically coupled microbeams with distributed electrodes has been theoretically investigated and then introduced in high sensitivity mass sensor. A reduced-order model of such sensor considering geometric and electrostatic nonlinearity is established to analyze the complex influences of coupling strength, coupling mode and actuation forces on the coupling dynamics. The sensitivity can be increased by nearly two times comparing with the traditional sensor with full electrodes operating in third-order mode. Furthermore, the sensitivity is increased by an order of magnitude compared to that of the first-order mode. Moreover, the sensitivity can be enhanced by four orders of magnitude compared to the output metric of frequency shift per unit mass, which significantly validated the effectiveness of using high order mode localization to improve sensor performance. Finally, the effects of the driving and coupling voltages on sensitivity are investigated to avoid mode aliasing.